MAPPING METAPHORIC AND NATURALISTIC ECOLINGUISTIC DIMENSIONS IN LEARNING THE INDONESIAN LANGUAGE AT THE UNIVERSITY: PEMETAAN DIMENSI-DIMENSI EKOLINGUISTIK METAFORIS DAN NATURALISTIK DALAM PEMBELAJARAN BAHASA INDONESIA DI PERGURUAN TINGGI - Agata Krismonita Permatasari; Remigius Kunjana Rahardi (LLDIKTI Wilayah X, 2022)
This study aims to describe the mapping of metaphorical and naturalistic ecolinguistic dimensions in Indonesian language learning in universities. The type of research used in this research is the descriptive qualitative method. The instrument in this research is the human instrument, namely the researcher himself. Data collection using the free-to-conversation listening method by using note-taking techniques as a follow-up. qualitative interactive analysis technique and there are several stages, namely the activities of reduction, presentation, and conclusion. The results of this study indicate that the form of the study of ecolinguistic dimensions in Indonesian language learning in universities is integrated into the form of inserting scientific texts that discuss local wisdom and mentioning the names of flora/fauna. The insertion of these texts was mapped into two categories, the text containing the metaphorical ecolinguistic dimension about activities related to local wisdom in learning the report text material and the second mapping, namely the naturalistic ecolinguistic dimension which discussed the meaning of flora/fauna embedded in naming people in Javanese culture. Then, the relevance of the study of ecolinguistic dimensions in Indonesian language learning can develop character and restore interaction, interrelation, and interdependence with the student's living environment.